Knowledge and Adoption of Bt Cotton Cultivation Practices - H. D. Rajput and Umesh R. Chinchmalatpure, (Indian Journal of Extension Education, 2016)
The present study was conducted in Jalgaon and Dhule district of North Maharashtra, with a random sample of 175 Btcotton growers, to measure the level of knowledge of Bt cotton growers and to understand the relationship betweenselected characteristics of Bt cotton growers and their extent of adoption. The results indicate that majority of therespondents had medium (53.71 per cent) level of adoption towards cultivation practices of Bt cotton. The analysis ofcorrelation revealed that variables viz., education, area under Bt cotton, annual income, socio-economic status, socialparticipation, scientific orientation, cosmopoliteness, extension contact and knowledge had positive and significantinfluence on their level of knowledge.